High and outside - Due, Linnea A. (San Francisco : Spinsters/Aunt Lute, 1988)
Star of her school softball team and with the highest point average in her class, Niki nonetheless has a severe drinking problem, and after nearly self-destructing decides to help herself.
Keywords: Alcoholism -- Fiction